Aligning Developmental Programs to Implement SDGs in India: Challenges and the Way Forward - Kumar, Prashant; Kumar, Kishore; Mathur, Shephali; Singh, Meenakshi (The journal of contemporary issues in business and government, 2021)
United Nations Agenda 2030 for sustainable development provides seventeen sustainable development goals (SDGs) to be achieved by 2030. India also committed to SDGs and signed the declaration to implement SDGs in the year 2015. India being home to one of the largest poor population in the world, the success of Agenda 2030 to large extent depends upon how India implements and achieves its SDGs targets. To this end, the Government of India has integrated SDGs with the national policy framework to achieve the targets of SDGs. Now, the development agenda of India primarily focus on five P’s- People, Planet, Peace, and Prosperity & Partnership. The present study provides insights into the progress being made by India to achieve SDGs through the review of various development programs. This paper maps various government schemes and development programs being implemented to achieve SDGs in India. Further, the paper also presents key bottlenecks and execution challenges to implement and achieve SDGs targets in India.